Grounding of modern model of informative providing, ecological defence and bioethical development of population of territories, polluted by radio-active matters - I. V. Kochin; O. M. Akulova; P. I. Sidorenko; V. M. Vasilenko; O. O. Gajvolya; V. M. Il'ina; T. M. Gut; I. F. Shilo; D. O. Troshin (Zaporozhye State Medical University, 2014)
Aim. Environmental protection and the bioethical development of population should be studied on the basis of modern paradigm that actualizes and allows to create new forms and organizational structures on the local level for population provision of reliable information. Purpose of the study is the development of new form and organizational structure model of local government's information activities. Methods and results. With this aim the materials of environmental radiation monitoring have been analyzed, using analytical-comparative method and content-analysis. It has been established that representatives of central and local authorities do not pay enough attention to the issues of informing the population about the environmental and radiological situation. Conclusion. This indicates insufficient providing of population with objective information and a need of integrated information system creation in the organizational form of Centers for environmental protection, biological ethics and territories development.